2017
DOI: 10.3389/fneur.2017.00712
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Severely Drug-Refractory Epilepsy: A Comparative Longitudinal Evaluation of Mortality, Morbidity, Resource Use, and Cost Using German Health Insurance Data

Abstract: PurposeTo evaluate long-term outcome of three years and treatment patterns of patients suffering from severely drug-refractory epilepsy (SDRE).MethodsThis analysis was population-based and retrospective, with data collected from four million individuals insured by statutory German health insurance. ICD-10 codes for epilepsy (G40*) and intake of anticonvulsants were used to identify prevalent cases, which were then compared with a matched cohort drawn from the population at large. Insurance data were available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 73 publications
6
66
0
6
Order By: Relevance
“…The benefits of GDNF also appeared to extend beyond a simple symptomatic effect as it extended, even if in a less robust manner, well beyond removal of the devices. The concept of a potential disease-modifying effect is further supported by the observation that the reduction in seizure frequency was accompanied by improvements in cognition and anxiety, both significant comorbidities of epilepsy (Strzelczyk et al, 2017;Michaelis et al, 2018). These benefits occurred without classic signs of mistargeted neurotrophic factor delivery such as alterations in food consumption, changes in daily activity, or other overt neurobehavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of GDNF also appeared to extend beyond a simple symptomatic effect as it extended, even if in a less robust manner, well beyond removal of the devices. The concept of a potential disease-modifying effect is further supported by the observation that the reduction in seizure frequency was accompanied by improvements in cognition and anxiety, both significant comorbidities of epilepsy (Strzelczyk et al, 2017;Michaelis et al, 2018). These benefits occurred without classic signs of mistargeted neurotrophic factor delivery such as alterations in food consumption, changes in daily activity, or other overt neurobehavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…Using US health insurance claim data, Cramer et al reported that adults with uncontrolled epilepsy (added AEDs to existing therapy) had higher annual overall (medical and pharmacy) costs and epilepsyrelated costs than those with well-controlled epilepsy (no change in AED therapy) over a one-year period [3]. Similarly, using German health insurance data, Strzelczyk et al reported that patients with severe drug-refractory epilepsy had increased rates of hospitalization, with increased morbidity and mortality rates compared with the general population [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in contrast to the perceived excellent prognosis, up to 20% of GGE patients remain refractory to AEDs . Overall, patients with drug‐refractory epilepsies are affected by increased morbidity and mortality, social stigma, reduced employment opportunities, and impaired quality of life for both themselves and their caregivers . Introduction of a new AED provides an opportunity to achieve better seizure control for some patients .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Overall, patients with drug-refractory epilepsies are affected by increased morbidity and mortality, social stigma, reduced employment opportunities, and impaired quality of life for both themselves and their caregivers. [8][9][10][11][12] Introduction of a new AED provides an opportunity to achieve better seizure control for some patients. 13,14 Data on treatment of GGE with newer drugs not yet approved for treatment of GGE, such as lacosamide, zonisamide, and brivaracetam (BRV), remain scarce.…”
Section: Introductionmentioning
confidence: 99%